Effect of Regional Expenditures, Population and PDRB (ADHB) Against the Original Revenue of Jambi Province - ., Sudirman; ., Susilawati (KnE Social Sciences, 2019)
This study aims to determine how much inﬂuence the number of populations, government expenditure and GRDP affect regional income in Jambi Province. This study uses a quantitative descriptive method with a form of correlational research that explains the relationship of independent variables with dependent variables. The analytical tool in this study uses multiple regression with proof of hypotheses by statistical tests t. Based on the results of SPSS calculations, the authors get the results of research in the form of government expenditure variables, PDRB and the number of residents together - they have a partially positive inﬂuence on regional income in Jambi Province due to F count (11.69973)>F table (3.41) then ho is rejected or equal to zero. This means that all regression coefﬁcients or all government expenditure variables, GDP and population together - have an effect on regional income in Jambi Province. From the results of the analysis in this study can be concluded, together the Regional Expenditure Variables, Population and GRDP affect Regional Original Revenue. Individually, the Regional Expenditure Variables, Population and GRDP can inﬂuence Regional Original Income, which has the greatest inﬂuence on Regional Original Revenue in Jambi Province.